“Doing gender” by sharing: examining the gender gap in the European sharing economy - Thomas Eichhorn; Christian Hoffmann; Katharina Heger (Internet Policy Review)
In this study, based on survey data collected from twelve European countries (N=6111), we build on the digital technology access model to examine the role of gender in access to the sharing economy. Applying a “doing gender” perspective, we find that men capitalise on a stronger economic position and a more pronounced orientation to explore new technology to gain access to sharing services, while women rely more on cultural and social capital. We relate our findings to intersectionality theory by discussing how class and gender intersect in facilitating access to the sharing economy.